Engage, Enrich, Enlighten, Energize: Explorations in Instructional Humor - Van der Veer Martens, Betsy (My University, 2021)
This chapter describes the use of classroom humor in the teaching of a government information course, employing the four Es (engage, enrich, enlighten, energize) to educate and empower library & information science students in a proactive approach to government information in order to help their communities both understand and make better use of these critical information resources, which are intended to facilitate the government "of the people, by the people, and for the people."
Keywords: Library & Information Science; Government Information; Teaching; Humor